HUBUNGAN ASUPAN ZAT GIZI MAKRO DENGAN STATUS GIZI REMAJA PUTRI DI SMK N 05 KOTA PALEMBANG - Indah Yuliana; Dian Safriantini; Mona Lestari (UHAMKA PRESS, 2022)
Currently, Indonesia has a triple burden of nutritional problems, namely stunting, wasting and obesity as well as micronutrient deficiencies such as anemia. This study aims to analyze the relationship between intake of macronutrients and nutritional status based on BMI. This study uses a cross sectional design. Data collection was carried out in September-October 2021 in Palembang with a sample of 129 young women selected by purposive sampling. The variables to be examined in this study were the nutritional status of female adolescents based on BMI, while energy, protein, fat and carbohydrate intake was measured using the semi-quantitative food frequency questionnaire method. Data analysis used the Chi Square test to see the relationship between variables. The results of the analysis showed that there was a relationship between protein intake and the nutritional status of female adolescents (p<0.05), while energy, carbohydrate and fat intake were not related to nutritional status (p> 0.05). This proves that protein intake is very important for young women to support growth.